Plan estratégico para desarrollar ventaja competitiva en la carrera de ingeniería comercial de la universidad técnica de cotopaxi en el periodo 2014-2017 - Guatasaca Collantes, Gabriela del Consuelo (2015)
The development of this work aims to design a strategic plan that achieves a competitive advantage in the Race of Commercial Engineering at the Technical University of Cotopaxi. This research is to conduct a situational analysis on which to identify the main existing advantages and critical points. For which it will begin with the development of the theoretical foundation encompassing variables, which are under study. The research methodology applied is based on field research, product of this analysis and interpretation of results is clear, which will serve as a cornerstone to develop strategies for generating improved competitive advantage which are: design of a library system Open shelf, developing training plans, conducting science and technology fairs….